Influence of subsonic aero engine design and flight routes on atmospheric pollution - Le Dilosquer, Marc (Cranfield University, 1998)
Gas turbine engine NOX, CO2 and H20 exhaust emissions from civil subsonic fleets are potentially in sufficient amounts to affect atmospheric ozone and climate, particularly with the projected growth in air traffic. Because, it may be that the future envisaged low-NOX combustor technologies may not keep up with the industry requirements for increased engine thermal efficiency, the potential benefits from optimising aero engine cycles and flight operations for low mission emissions deserve to be thoroughly investigated. The SKY computer simulation system developed to examine such alternative routes integrates flight route performance, aero engine performance and the formation of pollutants within the combustor. Based on Turbomatch, Cranfield Gas Turbine Simulation System, SKY can be used to optimise mission/aircraft/engine/combustor combinations with respect to landing and take-off (LTO) as well as mission emissions. A model of the high capacity Boeing 747-400 powered by Turbomatch high bypass ratio turbofan models and simulated on long range routes such as London-Tokyo is selected for this work. On the one hand, aero engine cycles can be designed at a optimum bypass ratio and deliver mission NOX reductions of up to 10% over designs optimised for LTO NOX, indicating that the current ICAO regulatory regime is a inadequate parameter to control mission NOX. On the other hand, operational measures such as speed reductions could bring further reductions of the order of 10%, but some of the improvement would be made at the expense of fuel burn, CO2 and H20 emissions, payload-range capability and direct operating costs. The benefits from such alternative routes are not negligible but smaller in comparison to the 30 to 80% potential cuts from future low-NOX technology, as well as to the 30% reduction due to expected improvements in the next 20 years or so in airframe weight and aerodynamics and more efficient navigation practices.